“Breaking the law” in dreams: analysis of a long dream series - Schredl, Michael (International journal of dream research, 2021)
Nightmares in which the dreamer performs a criminal act and is terrified of being punished have been reported in the literature. Systematic studies of “breaking the law” within dreams, however, are still lacking. Within a long dream series of N = 11,808 dreams, 0.80% of the dreams included some criminal activity often associated with the fear of being arrested; rarely with the feeling of remorse. Studying this dream type offers an opportunity to shed light on the options concerning how dreams might be related to waking-life: thematic continuity, e.g., being dishonest in waking-life and being dishonest in dreams; emotional continuity, e.g., the fear of being found out in the dreams is related to waking-life worries about possible negative evaluations by others; and/or metaphorical continuity, “killing” as a metaphor for ending relationships. Thus, this pilot study provided hypotheses for more in-depth analyses of larger dream samples.
Gesehen am 21.04.2021